Cardiac changes in pediatric cancer survivors. (December 2020) - Mokshagundam, Deepa; Olivieri, Laura J; McCarter, Robert; Kim, Aerang; Sable, Craig A; Spurney, Christopher F; Dham, Niti
Cardiac damage from chemotherapy is a known phenomenon leading to significant morbidity and mortality in the cancer surviving population, and identifying high-risk pediatric patients early is challenging. The purpose of this pilot study was to evaluate whether echo strain, cardiac MRI (CMR), and serum biomarkers are more sensitive methods for detecting cardiac toxicity than standard echo and to examine the relationship between biomarkers in patients without decreased systolic function as determined by standard echo. In this pilot study, we prospectively enrolled pediatric subjects after completion of anthracycline inclusive chemotherapy. Each subject underwent a post-treatment echocardiogram (standard with strain), serum biomarkers (N-terminal brain natriuretic peptide (NT-pro-BNP) and interleukin 1 receptor-like 1 protein (ST2)), and CMR (standard and extracellular volumes (ECVs)). We correlated the markers using Pearson correlation. We enrolled 30 subjects, 11F/19M, aged 8–21 years. Cumulative anthracycline dose (CAD) correlated with BNP (p=0.06), CMR ECV 4-chamber (p=0.05) and sagittal (p=0.01), and mitral valve E/A (p=0.02). BNP correlated with CMR ECV 4-chamber (p=0.001) and sagittal (p=0.001) and with echo average longitudinal strain (ALS) (p=0.05). This study demonstrated a significant correlation of CAD with BNP and CMR ECV. There was also a significant correlation of NT-pro-BNP with CMR ECV and ALS. Combining these parameters with standard echo has the potential to identify high-risk patients early. Further studies are needed for long-term follow-up and management in this vulnerable population.